((Denotations Of Meaning)) Sixth Section of Deliberative Indices: An Applied Study of The Indicative Manifestations Of (That) And Its Suffixes in The Qur’anic Discourse - Albaldawi, Jinan Salim Mohammad (Al-Adab Journal, 2022)
When we saw that the five sections of the pragmatic denotations - according to Levinson - did not include what refers to the meaning of their expressions, we proceeded to hold this study to be a sixth and complementary section to those sections, so we called it (Denotations of Meaning). The speaker’s attitude towards these meanings, and after setting the controls and limits of this new section, I took care to study it in the Qur’anic discourse, choosing (that) and its appendices as a model, indicating that this use of (that) is included in its figurative uses; Because it refers to the intangible (meanings), and the research concluded that the indicative manifestations of alienation in (that) differ according to the verbal context in which it is located; Sometimes the speaker wants to glorify, intending to urge and incite, or remind and threaten, or encourage and advise, and other times he wants to emphasize in a way of exaggeration, and another by which he wants to belittle, intending to warn, and he also concluded that its coming is identical to the addressee is meant to distance and address. Together for a deliberative intent, either to include the addressees alike, or to honor them, or to increase alertness to them as well as to others, or to include every recipient in every time and place.